Comparative finite element modelling of aneurysm formation and physiologic inflation in the descending aorta. Issue 15 (18th November 2019) - de Gelidi, Serena; Bucchi, Andrea
Abstract: Despite the general interest in aneurysm rupture prediction, the aneurysm formation has received limited attention. The goal of this study is to assess whether an aneurysm may be instigated in a healthy model of an aorta inflated by a supra-physiological pressure. The effect of two main aspects on numerical predictions has been explored: i) the geometric design and ii) the constitutive law adopted to represent the material properties. Firstly, higher values of wall stress and displacement magnitude were generated in the physiologic model compared to the cylindrical one when assigning the same material properties. Secondly, greater deformations are observed in the anisotropic model compared to the isotropic one.